Implementation of new varieties into the production on the base of accelerated system of their reproduction - В. В. Шелепов; В. М. Лисікова (Plant Varieties Studying and Protection)
The system of accelerated seed reproduction for new variety of winter wheat Krizhinka, and its application into production during years 1997-2000, are adduced in the article. Application of this system allowed in year 2000 to grow about 20 thousands metric centner of original seeds, and to increase the planted area at the time of including of the variety to State Register of Plant Varieties of Ukraine till 50 thousand he.